Unique and Shared Functions of Nuclear Lamina LEM Domain Proteins in Drosophila. - Barton, L.J.; Wilmington, S.R.; Martin, M.J.; Skopec, H.M.; Lovander, K.E.; Pinto, B.S.; Geyer, P.K. (Genetics, 2014)
The nuclear lamina is an extensive protein network that contributes to nuclear structure and function. LEM domain (LAP2, emerin, MAN1 domain, LEM-D) proteins are components of the nuclear lamina, identified by a shared ?45-amino-acid motif that binds Barrier-to-autointegration factor (BAF), a chromatin-interacting protein. Drosophila melanogaster has three nuclear lamina LEM-D proteins, named Otefin (Ote), Bocksbeutel (Bocks), and dMAN1. Although these LEM-D proteins are globally expressed, loss of either Ote or dMAN1 causes tissue-specific defects in adult flies that differ from each other. The reason for such distinct tissue-restricted defects is unknown. Here, we generated null alleles of bocks, finding that loss of Bocks causes no overt adult phenotypes. Next, we defined phenotypes associated with lem-d double mutants. Although the absence of individual LEM-D proteins does not affect viability, loss of any two proteins causes lethality. Mutant phenotypes displayed by lem-d double mutants differ from baf mutants, suggesting that BAF function is retained in animals with a single nuclear lamina LEM-D protein. Interestingly, lem-d double mutants displayed distinct developmental and cellular mutant phenotypes, suggesting that Drosophila LEM-D proteins have developmental functions that are differentially shared with other LEM-D family members. This conclusion is supported by studies showing that ectopically produced LEM-D proteins have distinct capacities to rescue the tissue-specific phenotypes found in single lem-d mutants. Our findings predict that cell-specific mutant phenotypes caused by loss of LEM-D proteins reflect both the constellation of LEM-D proteins within the nuclear lamina and the capacity of functional compensation of the remaining LEM-D proteins.